(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article examines the problem of corruption as a transnational crime causing a global crisis. It analyzes the experience of various countries in the fight against corruption, including the UK, Scandinavia, Hong Kong, the USA, Singapore, Japan and the Netherlands. It discusses the legislative measures taken in these countries to combat corruption, such as the Bribery Act in the UK and the Foreign Corrupt Practices Act in the USA. It also emphasizes the importance of public control and ethical standards in reducing the level of corruption. The article emphasizes that a successful fight against corruption requires a comprehensive approach, including both legislative initiatives and the active participation of civil society.